Odpowiedź:
a)
(6x - 2)/4 = 3 | * 4
6x - 2 = 4 * 3 = 12
6x = 12 + 2 = 14
x = 14/6 = 2 2/6 = 2 1/3
b)
4(1 - x) + 2 = - 7
4 - 4x = - 7 - 2
4 - 4x = - 9
- 4x = - 9 - 4
- 4x = - 13
4x = 13
x = 13/4 = 3 1/4
c)
5 - (3 - 4x) = 5(1 - x)
5 - 3 + 4x = 5 - 5x
2 + 4x = 5 - 5x
4x + 5x = 5 - 2
9x = 3
x = 3/9 = 1/3
d)
- 5 - 3(x + 1) = - (- 4x + 1)
- 5 - 3x - 3 = 4x - 1
- 8 - 3x = 4x - 1
- 3x - 4x = - 1 + 8
- 7x = 7
7x = - 7
x = - 7/7 = - 1
e)
(3x - 5)/8 = 1/4 + x | * 8
3x - 5 = 1/4 * 8 + 8x
3x - 5 = 2 + 8x
3x - 8x = 2 + 5
- 5x = 7
5x = - 7
x = - 7/5 = - 1 2/5 = - 1,4